Effect of diuretic down-titration on pulmonary congestion assessed by lung ultrasound when introducing sodium-glucose cotransporter 2 inhibitors. (3rd October 2022) - Domingo, M; Teis, A; Alonso, N; Julian, T; Bares, D; Barcelo, E; Revuelta-Lopez, E; Gonzalez, B; Codina, P; Cediel, G; Santiago-Vacas, E; Santesmases, J; et al.
Abstract: Background: Mechanistic pathways of sodium-glucose cotransporter 2 inhibitors (SGLT2i) benefits in heart failure (HF) remain unclear. Purpose: To investigate the effects of SGLT2i and simultaneous diuretic down-titration on pulmonary congestion assessed by lung ultrasound (LUS) and by HF biomarkers. Methods: Prospective observational study in outpatients with HF and type 2 diabetes assigned to a SGLT2i. LUS was performed at baseline (just before starting SGLT2i), at 15 days and at 3-months of follow-up. Eight thoracic areas were examined. Diuretic regime was reduced at baseline, when LUS and clinical assessment allowed. The main outcome was short-time change in B-lines sum. Secondary endpoints evaluated N-terminal pro-B-type natriuretic peptide (NTproBNP), cancer antigen 125 (CA125) and interleukin-1 receptor-like 1 (ST2) Results: 88 patients were included (age, 66.8±9.9 years; 93.2% male; 77.3% in NYHA II functional class; 75% treated with loop diuretics). The median of lines B was 2 (RIQ 1–4), 2 (RIQ 1–4) and 2 (RIQ 0–4) at the initial visit, 15 days and 3 months, respectively (initial vs. 3 months, p=0.21) (Table 1). The number of patients treated with loop diuretics decreased from 66 to 33 (p<0.001) and the mean dose of furosemide (or equivalent) in those who continued decreased from 61±5 mg/day to 45.8±20 mg/day (p<0.001). There were no hospitalizations for HF in the 3 months of follow-up. None of the biomarkers showed statistically differences at 3 months of follow-up (Table 1). Conclusions: The introduction of SGLT2i allowed a significant reduction of diuretics in chronic HF patients and diabetes, without evidence of worsening lung congestion assessed neither by LUS nor by HF biomarkers. Funding Acknowledgement: Type of funding sources: None.